2013
DOI: 10.1111/phn.12047
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding: A holistic Concept Analysis

Abstract: Breastfeeding is a critical public health intervention. Nurses play a vital role in promoting and supporting optimal breastfeeding practices in infants and young children. An analysis following the eight-part Walker & Avant method provides clarity and context to the concept of breastfeeding. The antecedents of the concept of breastfeeding indicate nurse interventions to facilitate and the consequences provide key points for education related to the benefits of breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 72 publications
0
27
0
3
Order By: Relevance
“…It is considered that some recommendations and considerations, derived from the results of the present research, are important: (1) it is important to understand that the breastfeeding process is dynamic and, as such, the evaluations and the diagnostic judgment can undergo modifications as a function of time in which the data is collected;(2) the defining characteristics usually do not dispose alone of predictive power or sufficient explanation so that the nurse can elaborate an accurate clinical judgment only with an indicator being expected that a greater number of characteristics are investigated and gathered for a more precise judgment on the occurrence or not of ineffective breastfeeding;(3) to experiment with the construction of models of clinical indicators (defining characteristics) and rules of use that are capable of better representing the relationships between them and the diagnosis to be characterized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered that some recommendations and considerations, derived from the results of the present research, are important: (1) it is important to understand that the breastfeeding process is dynamic and, as such, the evaluations and the diagnostic judgment can undergo modifications as a function of time in which the data is collected;(2) the defining characteristics usually do not dispose alone of predictive power or sufficient explanation so that the nurse can elaborate an accurate clinical judgment only with an indicator being expected that a greater number of characteristics are investigated and gathered for a more precise judgment on the occurrence or not of ineffective breastfeeding;(3) to experiment with the construction of models of clinical indicators (defining characteristics) and rules of use that are capable of better representing the relationships between them and the diagnosis to be characterized.…”
Section: Resultsmentioning
confidence: 99%
“…From a conceptual point of view, it can be understood as a biopsychosocial process of dynamic relationship between a woman and a child, which is initiated at a specific interval after birth, with different levels of efficacy in terms of provision and breastmilk receiving during each feeding session (1) . In Brazil, the Ministry of Health, dealing with the nutrition of the child in a publication addressed to primary care, recognizes that breastfeeding is much more than nurturing and highlights the role of the health professional to increase breastfeeding rates in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Although a preponderance of evidence documents the benefits of breastfeeding, complications associated with studying human populations limit precise determination of the specific biological processes or factors that underlie these benefits. Socioeconomic status and maternal education are known confounding factors that influence outcomes in studies of human subjects, in addition to maternal health, feeding pattern, and duration of exclusive feeding [23, 24]. Biological, socioeconomic, and psychosocial factors, in addition to breastfeeding [25], have also been found to relate to behavioral measures in large-scale, population-based cohort infant studies, while other studies have identified that social and home environmental factors heavily mediate the relationship between cognitive performance and breastfeeding [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…Lactation has been a critical public health intervention [9]. The World Health Organization [10] recommends exclusive breast-feeding for the first six months of life and continued breast feeding up to two years of age or beyond.…”
Section: Literature Reviewmentioning
confidence: 99%